2010
DOI: 10.1530/eje-10-0094
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin affects the hypothalamus–pituitary–thyroid axis in humans by increasing free thyroxine and decreasing TSH in plasma

Abstract: Objective: Ghrelin promotes a positive energy balance, e.g. by increasing food intake. Stimulation of the activity of the hypothalamus-pituitary-thyroid (HPT) axis promotes a negative energy balance, e.g. by increasing energy expenditure. We therefore hypothesized that ghrelin suppresses the HPT axis in humans, counteracting its energy-saving effect. Design and methods: In this single-blind, randomized, cross-over study, we determined secretion patterns of free triiodothyronine (fT 3 ), free thyroxine (fT 4 ),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 63 publications
(74 reference statements)
2
37
0
1
Order By: Relevance
“…The trijodothyronine (fT 3 ) and thyroid-binding globulin (TBG) were not affected (Kluge et al, 2010b). These findings support the hypothesis that ghrelin suppresses the HPT axis in humans, which counteracts its energy-saving effects.…”
Section: -Please Insert Figures 1 and 2 Near To Here -supporting
confidence: 66%
“…The trijodothyronine (fT 3 ) and thyroid-binding globulin (TBG) were not affected (Kluge et al, 2010b). These findings support the hypothesis that ghrelin suppresses the HPT axis in humans, which counteracts its energy-saving effects.…”
Section: -Please Insert Figures 1 and 2 Near To Here -supporting
confidence: 66%
“…These results has been supported by a study from our research group which have demonstrated that, effectively, ghrelin has a direct effect on the three tissue-specific genes involved in thyroid hormone synthesis: thryroperoxidase (TPO), Na + /I -symporter (NIS) and thyroglobulin [144,145]. This direct effect on follicular-cell activity could be responsible for the effects observed at the hypothalamus-pituitary-thyroid axis [144,145].…”
Section: Ghrelinmentioning
confidence: 69%
“…In regard to the implication of ghrelin in thyroid hormone synthesis, after the demonstration of the ghrelin receptor in human thyroid tissue [143], Kluge et al [144] described a ghrelinmediated decrease in TSH levels and an increase of serum T4, probably due to a ghrelin direct stimulatory action on the thyroid gland. These results has been supported by a study from our research group which have demonstrated that, effectively, ghrelin has a direct effect on the three tissue-specific genes involved in thyroid hormone synthesis: thryroperoxidase (TPO), Na + /I -symporter (NIS) and thyroglobulin [144,145].…”
Section: Ghrelinmentioning
confidence: 99%
“…Specifically, AG administration was shown to inhibit LH release in rats (Furuta et al 2001, Fernandez-Fernandez et al 2005, and FSH and LH in healthy men (Kluge et al 2007, Lanfranco et al 2008, Kluge et al 2009) and women (Messini et al 2010a, Kluge et al 2012. On the other hand, the role of AG on TSH release is not well defined as some studies indicate a lack of direct effect on TSH release in humans (Takaya et al 2000, Hataya et al 2001, Nagaya et al 2001, while a recent study indicates that AG administration could induce a decrease in TSH release in healthy subjects (Kluge et al 2010). Given that this study showed that AG was able to increase thyroxine, the authors speculate that the effect of AG on TSH might be mediated by a indirect action at the hypothalamic level through a thyroxine-dependent feedback (Kluge et al 2010).…”
Section: Observations)mentioning
confidence: 99%
“…On the other hand, the role of AG on TSH release is not well defined as some studies indicate a lack of direct effect on TSH release in humans (Takaya et al 2000, Hataya et al 2001, Nagaya et al 2001, while a recent study indicates that AG administration could induce a decrease in TSH release in healthy subjects (Kluge et al 2010). Given that this study showed that AG was able to increase thyroxine, the authors speculate that the effect of AG on TSH might be mediated by a indirect action at the hypothalamic level through a thyroxine-dependent feedback (Kluge et al 2010). Finally, glycoprotein hormones a chain (CGA) is the common subunit for FSH, LH, and TSH (and chorionic gonadotropin hormones) and is normally released as part of a heterodimer with these b subunits.…”
Section: Observations)mentioning
confidence: 99%